2020
DOI: 10.1111/jgh.14979
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous 8‐hydroxydeoxyguanosine ameliorates liver fibrosis through the inhibition of Rac1‐NADPH oxidase signaling

Abstract: Background and Aim Exogenous 8‐hydroxydeoxyguanosine (8‐OHdG) was suggested as an inhibitor of Rac1 and NADPH oxidase (NOX). The aim of this study was to evaluate the effects of the exogenous 8‐OHdG on hepatic fibrogenesis in vitro and in vivo model of liver fibrosis. Methods Adult Sprague–Dawley rats were allocated to sham‐operated rats (n = 7), rats that underwent bile duct ligation (BDL) (n = 6), and BDL rats treated with 8‐OHdG (60 mg/kg/day by gavage, n = 6). All rats were sacrificed on day 21. Double imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
(65 reference statements)
2
4
0
Order By: Relevance
“…Our results addressed exogenous oh8dG as a protective supplement against potential HTK-solution-mediated oxidative damage. Thus, our observations in cardiac tissues are consistent with previous studies in various experimental systems showing the protective role of exogenous oh8dG against oxidative or inflammatory signals [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results addressed exogenous oh8dG as a protective supplement against potential HTK-solution-mediated oxidative damage. Thus, our observations in cardiac tissues are consistent with previous studies in various experimental systems showing the protective role of exogenous oh8dG against oxidative or inflammatory signals [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Discussionsupporting
confidence: 92%
“…The biomarker 8-hydroxy-2′-deoxyguanosine (oh8dG) is a naturally driven oxidized nucleic acid or a product of oxidant-mediated DNA damage [ 20 ]. Various studies have reported that oh8dG also exhibits anti-oxidative effects and is a biomarker of oxidative stress in numerous tissues, and administration of exogenous oh8dG involves the inhibition of inflammatory cascade including Rac-GTP, ROS, and NF-κB signaling [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…30 Shin et al found that exogenous 8-hydroxydeoxyguanosine ameliorated liver brosis by inhibiting RAC1-NADPH oxidase signaling. 31 The conclusion from the available studies that RAC1 is a key gene in brosis is consistent with the results of our analysis. This not only indicates that RAC1 is a promising therapeutic target in cirrhosis, but also demonstrates the reliability of our analysis results.…”
Section: Discussionsupporting
confidence: 92%
“…Inhibition of endoplasmic reticulum‐derived ROS also alleviated the liver fibrosis. Shin et al stated that exogenous 8‐hydroxydeoxyguanosine ameliorated liver fibrosis by inhibiting the NADPH oxidase signalling 51 . A plethora of the study suggests that the excessive production of ROS is associated with the pro‐inflammatory signalling pathways activation.…”
Section: Discussionmentioning
confidence: 99%